Cymbopogon citratus (DC.) Stapf aqueous extract ameliorates loperamide-induced constipation in mice by promoting gastrointestinal motility and regulating the gut microbiota - Gao, Xiaoyu; Hu, Yifan; Tao, Yafei; Liu, Shuangfeng; Chen, Haowen; Li, Jiayi; Zhao, Yan; Sheng, Jun; Tian, Yang; Fan, Yuanhong (Frontiers in Microbiology, 2022)
Slow transit constipation (STC) is the most common type of functional constipation. Drugs with good effects and few side effects are urgently needed form the treatment of STC. Cymbopogon citratus (DC.) Stapf (CC) is an important medicinal and edible spice plant. The wide range of biological activities suggested that CC may have laxative effects, but thus far, it has not been reported. In this study, the loperamide-induced STC mouse model was used to evaluate the laxative effect of the aqueous extract of CC (CCAE), and the laxative mechanism was systematically explored from the perspectives of the enteric nervous system (ENS), neurotransmitter secretion, gastrointestinal motility factors, intestinal inflammation, gut barrier and gut microbiota. The results showed that CCAE not only decreased the serum vasoactive intestinal polypeptide (VIP), induced nitric oxide synthases (iNOS), and acetylcholinesterase (AchE) in STC mice but also increased the expression of gastrointestinal motility factors in colonic interstitial cells of Cajal (ICCs) and smooth muscle cells (SMCs), thereby significantly shortening the defecation time and improving the gastrointestinal transit rate. The significantly affected gastrointestinal motility factors included stem cell factor receptor (c-Kit), stem cell factor (SCF), anoctamin 1 (Ano1), ryanodine receptor 3 (RyR3), smooth muscle myosin light chain kinase (smMLCK) and Connexin 43 (Cx43). Meanwhile, CCAE could repair loperamide-induced intestinal inflammation and intestinal barrier damage by reducing the expression of the pro-inflammatory factor IL-1β and increasing the expression of the anti-inflammatory factor IL-10, chemical barrier (Muc-2) and mechanical barrier (Cldn4, Cldn12, Occludin, ZO-1 and ZO-2). Interestingly, CCAE could also partially restore loperamide-induced gut microbial dysbiosis in various aspects, such as microbial diversity, community structure and species composition. Importantly, we established a complex but clear network between gut microbiota and host parameters. Muribaculaceae, Lachnospiraceae and UCG-010 showed the most interesting associations with the laxative phenotypes; several other specific taxa showed significant associations with serum neurotransmitters, gastrointestinal motility factors, intestinal inflammation, and the gut barrier. These findings suggested that CCAE might promote intestinal motility by modulating the ENS-ICCs-SMCs network, intestinal inflammation, intestinal barrier and gut microbiota. CC may be an effective and safe therapeutic choice for STC.